Low risk PCNL patients' post operative infection rates with and without antibiotic prophylaxis - Vosianov, S. O; Gubar, A. O.; Bachurin, G. V.; Boiko, A. I.; Bachurin, V. I.; Dovbysh, M. A.; Dovbysh, I. M.; Губарь, Андрій Олександрович; Бачурін, Георгій Вікторович; Бачурін, Віктор Іванович; Довбиш, Михайло Афанасійович; Довбиш, Ігор Михайлович (Запорізький державний медичний університет, 2018)
Objectives. The aim of the study - to compare the post-operative fever rate in low risk patients underwent to percutaneous nephrolithotripsy with and without antibiotics. Materials & methods. The study was conducted in urology departments of Institute of Urology, Kyiv, Ukraine & “Motor Sich Clinic”, Zaporizhzhya, Ukraine. Institution Urology Departments collected prospectively data for two-years observations on patients treated with PCNL. Patients with negative urine culture growth were defined as being at low risk for post operative infections. Propensity score matching was done to achieve two groups with similar characteristics on diabetes mellitus status, the presence of nephrostomy drainage tube placed prior to PCNL, staghorn stone rate. Fever was used as a proxy for post operative infection. Post operative outcomes were compared between the two matched groups.
Keywords: тези доповідей